Strategy and command : the Anglo-French coalition on the Western Front, 1914 - Prete, Roy A. (Roy Arnold), 1943- (McGill-Queen's University Press, 2009)
Histories of the First World War are often written from a British perspective, ignoring the coalition element of the conflict and the French point of view. In Strategy and Command, Roy Prete offers a major new interpretation supported by in-depth research in French archival sources.